2022
DOI: 10.3390/diagnostics12092071
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: MRI, CEUS, and CT Imaging Features of Metanephric Adenoma with Histopathological Correlation and Literature Review

Abstract: The metanephric adenoma is an extremely rare, benign, embryonal-epithelial neoplasm of the kidney and has a good prognosis with appropriate treatment. It can present at any age and is often asymptomatic. Histologically, the lesion is well established; however, there have been only a few cases described with available detailed imaging findings, most of them with large renal masses typically depicted by computed tomography (CT). This case report includes imaging of contrast-enhanced MRI, contrast-enhanced ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…On magnetic resonance imaging (MRI), MAs have exhibited hypointense characteristics on T1-weighted imaging and either iso-or slightly hyperintense features on T2-weighted imaging [17]. In a review of 8 cases, Yan et al reported the MAs appeared isointense on both T1-and T2-weighted imaging [12].…”
Section: Discussionmentioning
confidence: 99%
“…On magnetic resonance imaging (MRI), MAs have exhibited hypointense characteristics on T1-weighted imaging and either iso-or slightly hyperintense features on T2-weighted imaging [17]. In a review of 8 cases, Yan et al reported the MAs appeared isointense on both T1-and T2-weighted imaging [12].…”
Section: Discussionmentioning
confidence: 99%
“…A metanephric adenoma is more common in females. Most of the tumors present as unilateral and unifocal, circumscribed but not encapsulated lesions [1].…”
Section: Introductionmentioning
confidence: 99%